Analisis Pengaruh Sistem Pentanahan Tower dan Sambaran Petir Terhadap Gangguan serta Evaluasi Efektivitas Metode Perbaikan Pertanahan pada SUTT 150 kV - Wyananda Fiqi Fadlan Adhima; Rummi Sirait (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The high frequency of lightning activity in Indonesia poses a significant threat to the reliability of power transmission systems. Based on operational data, the 150 kV Tanjung Jati–Sayung transmission line recorded the highest number of lightning-induced disturbances within the Semarang Transmission Maintenance Unit (UPT Semarang) during the 2021–2025 period, making it a relevant subject for further investigation. This study aims to analyze the relationship between lightning strike frequency, tower grounding resistance, and transmission system disturbances, as well as to evaluate the effectiveness of grounding system improvement methods that have been implemented. A quantitative approach was employed using descriptive analysis, Pearson correlation, and simple linear regression based on lightning strike data, tower grounding resistance measurements, and disturbance records. The results indicate that lightning strike frequency has a positive relationship with transmission system disturbances, with a correlation coefficient of 0.137 and a p-value of 0.0452. Similarly, tower grounding resistance exhibits a positive relationship with system disturbances, with a correlation coefficient of 0.2133 and a p-value of 0.0017. Although these relationships are statistically significant, the relatively low coefficient of determination (R² < 5%) suggests that both variables explain only a small portion of the variation in lightning-related disturbances, indicating the presence of other contributing factors that were not included in this study. Nevertheless, grounding system improvement remains one of the technical measures that can be optimized to reduce the risk of transmission line disturbances. The evaluation results show that towers employing the Multi Rod Grounding (MRG) method exhibited the lowest disturbance probability among the grounding improvement methods observed in this study. Overall, the findings provide empirical insights into the relationship between lightning strike frequency, tower grounding resistance, and transmission system disturbances, and may serve as a useful reference for developing maintenance strategies aimed at improving transmission system reliability.